Digitalizing Malay Medical Manuscripts: A Database-Driven Approach to Preservation, Knowledge Management and Intellectual Property - Fauzi, Nurulwahidah; Mohamed Najid, Mohamad Hafizuddin; Ibrahim, Norhasnira; Sahbudin , Murtadha Arif (Journal of Al-Tamaddun, 2025)
This study explores the digitalization and structured knowledge management of 18th to mid-19th century Malay medical manuscripts, integrating digital humanities and intellectual property considerations. The primary objective is to ensure the preservation, accessibility, and systematic organization of traditional Malay medical knowledge through the development of a structured digital database. To achieve this, the study is structured around three core objectives. First, extraction of Malay medical knowledge focuses on identifying and digitizing traditional medicinal treatments, herbal remedies, and compound formulations recorded in selected Malay medical manuscripts. Second, categorization and ontology development aim to systematically classify the extracted data based on herbal taxonomy, medicinal compounds, and therapeutic applications, using an ontology-based approach to enhance data searchability and knowledge representation. Third, database design and development involve creating an interactive and accessible digital repository using Protégé (ontology editor tool) and XAMPP. The findings indicate that the ontology-based classification has significantly improved the organization and retrieval of information from the manuscripts, offering a new avenue for research in traditional medicine and historical pharmacology. By preserving and structuring this knowledge digitally, the study enhances accessibility for researchers, medical historians, and practitioners, bridging the gap between traditional healing practices and modern medical research. Furthermore, by addressing legal and ethical considerations, this research contributes to the ongoing discussions on intellectual property protection and responsible knowledge sharing in the digital era. This study highlights the critical role of digitalization in safeguarding cultural heritage and ensuring the continued relevance of traditional Malay medical knowledge. By developing a structured digital repository, this research provides a sustainable framework for integrating historical medical wisdom into contemporary knowledge systems, ensuring its long-term preservation and accessibility.